Preliminary study on the effect of gamma radiation on the furniture carpet beetle anthrenus flavipes LeConte (Coleptera: Dermestidae) (Baghdad Science Journal, 2006)
Preliminary study on the possibility od using gamma radiation to induce sexual sterility in males of the furniture carpet beetle A. flavipes was carried out as a part of programme aiming to use SIT in controlling this pest.